Правові засади взаємодії суб’єктів владних повноважень щодо забезпечення реабілітаційної допомоги військовослужбовцям в Україні - Івахненко, О. А.; Ivakhnenko, O. A. (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 2 (109). - С. 156-166, 2025)
Наукове дослідження присвячено визначенню особливостей взаємодії різних органів влади для забезпечення надання реабілітаційної допомоги військовослужбовцям в Україні. Проаналізовано законодавчі та підзаконні акти, які регулюють відносини у сфері охорони здоров’я, а також повноваження окремих суб’єктів владних повноважень. Вивчено праці дослідників, присвячені проблемам надання реабілітаційної допомоги військовослужбовцям в Україні. Визначено напрями взаємодії органів влади під час надання реабілітаційної допомоги військовослужбовцям. Запропоновано зміни і доповнення до національного законодавства.

The scientific research is devoted to establishing the peculiarities of interaction between various authorities to ensure the provision of rehabilitation assistance to military personnel in Ukraine. Legislative and subordinate acts regulating relations in the field of healthcare and the powers of individual authorities have been studied. The works of researchers devoted to the problems of providing rehabilitation assistance to military personnel in Ukraine have been studied. It is noted that the legal regulation of the interaction of government authorities in providing rehabilitation assistance to military personnel in Ukraine involves establishing, in legislative and subordinate acts, the conditions for joint activities of government authorities in the field of medical rehabilitation, maintenance and material support of rehabilitation facilities, and the referral of military patients to healthcare institutions under other departmental subordination. It is concluded that Ukrainian legislation provides for the following areas of interaction between different authorities in the process of providing rehabilitation assistance: interaction between local state authorities and local self-government bodies on issues related to the maintenance of rehabilitation facilities and the provision of rehabilitation services; cooperation between the Ministry of Health of Ukraine and the Ministry of Social Policy of Ukraine with other authorities in the process of organising the work of rehabilitation facilities and providing persons with disabilities with rehabilitation aids; cooperation between militarised authorities in the process of providing rehabilitation assistance to military personnel in sanatorium and resort facilities of various subordination. It is noted that many militarised authorities have rehabilitation facilities under their jurisdiction, where military personnel can receive rehabilitation services. It is proposed to develop joint orders of the Ministry of Health of Ukraine and the military authorities regarding the provision of rehabilitation services to military personnel in stateowned healthcare institutions.
Legal basis for interaction between authorities in providing rehabilitation assistance to military personnel in Ukraine
Keywords: реабілітаційна допомога; взаємодія; орган влади; повноваження; правове регулювання; реабілітаційний заклад; суб’єкт владних повноважень; rehabilitation assistance; interaction; authority; powers; legal regulation; rehabilitation institution